Distinct protein forms are produced from alternatively spliced bicistronic glutamic acid decarboxylase mRNAs during development. - Szabo, G (1994)
It has been shown that the enzyme glutamic acid decarboxylase (GAD; EC 4.1.1.15), which catalyzes the conversion of L-glutamate to gamma-aminobutyric acid in the central nervous system of vertebrates, can be first detected in rodents at late embryonic stages. In contrast, we have found that the gene coding for the 67-kDa form of GAD is already transcriptionally active at embryonic day E10.5 in the mouse. In addition to the 3.5-kb adult-type mRNA, we have detected two 2-kb embryonic messages that contain alternatively spliced exons of 80 (I-80) and 86 (I-86) bp, respectively. The overlapping stop-start codon TGATG, found in the embryonic exons, converts the monocistronic adult-type transcript into a bicistronic one, coding for a 25-kDa leader peptide and a 44-kDa enzymatically active truncated GAD. A second stop codon at the 3' end of the 86-bp exon abolishes the expression of truncated GAD. The products of the two embryonic mRNAs were identified in a rabbit reticulocyte in vitro translation system, COS cells, and mouse embryos. The two GAD embryonic forms represent distinct functional domains and display characteristic developmental patterns, consistent with a possible role in the formation of the gamma-aminobutyric acid-ergic inhibitory synapses.